Formation and study of static and dynamic characteristics of electronically controlled diesel engine - Dumenko, P.; Kravchenko, Serhii; Prokhorenko, Andriy; Talanin, Dmytro (My University, 2019)
Manufacturing companies of electronic control systems of diesel engines protect access to a program operation algorithm of the regulator that makes impossible adjustments and settings of its work, for example, at reequipment or operational development of a new diesel engine. Therefore, it is important to acknowledge the solution of the scientific and technical problem of an effective and reliable system creation of electronic control of diesel fuel supply with an open program algorithm of its work. During the current research, settlement and experimental studies of a diesel engine supplied with a system of electronic control of a crankshaft rotation frequency developed by the authors show rather high adequacy in results. The dynamic mathematical model of the single-cylinder diesel engine supplied with the electronic regulator of rotation frequency has been developed and verified.
Keywords: diesel engine; electronic regulator; mathematical modelling